Asparagine assimilation is critical for intracellular replication and dissemination of Francisella. (8th November 2013) - Gesbert, Gael; Ramond, Elodie; Rigard, Mélanie; Frapy, Eric; Dupuis, Marion; Dubail, Iharilalao; Barel, Monique; Henry, Thomas; Meibom, Karin; Charbit, Alain
Summary In order to develop a successful infectious cycle, intracellular bacterial pathogens must be able to adapt their metabolism to optimally utilize the nutrients available in the cellular compartments and tissues where they reside. Francisella tularensis, the agent of the zoonotic disease tularaemia, is a highly infectious bacterium for a large number of animal species. This bacterium replicates in its mammalian hosts mainly in the cytosol of infected macrophages. We report here the identification of a novel amino acid transporter of the major facilitator superfamily of secondary transporters that is required for bacterial intracellular multiplication and systemic dissemination. We show that inactivation of this transporter does not affect phagosomal escape but prevents multiplication in the cytosol of all cell types tested. Remarkably, the intracellular growth defect of the mutant was fully and specifically reversed by addition of asparagine or asparagine‐containing dipeptides as well as by simultaneous addition of aspartic acid and ammonium. Importantly, bacterial virulence was also restored in vivo, in the mouse model, by asparagine supplementation. This work unravels thus, for the first time, the importance of asparagine for cytosolicmultiplication of Francisella. Amino acid transporters are likely to constitute underappreciated players in bacterial intracellular parasitism.